PERNYATAAN EMOSI BERBAHASA INDONESIA SISWA SMP DHARMA WIWEKA DENPASAR: KAJIAN PSIKOLINGUISTIK - Imaculda DC. Sarmento, Maria (Humanis; Volume 15. No.2. Mei 2016)
Communication which expressed by the students of Dharma Wiweka junior high school is verbal and nonverbal communication. Verbal and nonverbal language is used to communicate thoughts and feelings. Through dialogue in the form of a conversation from speaker to hearer directly or indirectly, written or oral. Emotional statement is expressed by anger, sadness, fear, and pleasure. Emotional statement in Indonesian language is determined by the value of intonation. Action and dialogue was assessed by psycholinguistic analyzing with situation approach which determines that the intonation of student’s statement, inner structure and structural relationship of birth and verbal and nonverbal factors affect the student.
Keywords: psycholinguistics, syntax and emotional statement